ANALISIS KONTRIBUSI PENDAPATAN WANITA BURUH TANI PADI SAWAH TADAH HUJAN TERHADAP PENDAPATAN KELUARGA DI DESA GUNUNG BATU KECAMATAN CEMPAKA KABUPATEN OGAN KOMERING ULU”. (JASEP, 2018)
Analysis of Rural Female Rice Farmers' Income Contribution to Revenue of Family in Gunung Batu Village, Cempaka Sub-district, East Ogan Komering Ulu Regency. where the determination of the area is done intentionally (purposive). This region is chosen as a research location because considering this area there are basic elements that will be studied, especially in terms of the role of women laborers of rain-fed rice paddies. Implementation of this research conducted in December 2016 - May 2017. The data obtained is tabulated and described descriptively and qualitatively. The research method used in this research is survey method used to obtain field facts by using questionnaire as data collection tool. Sampling method used in this research is census method as many as 30 samples from 150 farmers. The results of the research showed that (1) The average income of farmers in rainy rice field in Gunung Batu Village, Cempaka Sub-district, East Ogan Komering Ulu Regency is Rp 14,345 .400 per year, (2) The contribution of women farmers' income to rainfed lowland rice per year is 43.84 percent or Rp 14,345,400 from the total family income of Rp 32,718,733 per year